Work Related Stressors and Teachers’ Performance: Evidence from College Teachers Working in Punjab - Rizwan Qaiser Danish; Shumaila Qaseem; Tayyaba Mehmood; Qazi Muhammad Ali; Hafiz Fawad Ali; Rabia Shahid (European Scientific Journal, ESJ, 2019)
This study is conducted to determine the impact that job stress (job conflict, work overload, inadequate reward policy and job burnout) has on teacher’s job outcomes (employee loyalty and employee performance). In order to explain the relationship among the variables, hypothesis testing was used since the study is causal. This paper focuses on teachers of five best intermediate level colleges of Lahore and a sample size of 100 respondents. The independent variable of the study is work related stressors (job conflict, work overload, inadequate reward policy, and job burnout), while dependent variable is teachers’ performance (employee loyalty and employee performance). SPSS version 20 was used for the initial analysis of collected data (descriptive statistics, reliability analysis, and correlation). Furthermore, SEM using AMOS is applied for checking the fitness of the model as well as the relationship among dependent and independent variables. The analyzed results show impact of all independent variables on dependent variables. However, job conflict, job burnout, and inadequate reward policies have significant impact on teacher’s performance. The largest influence comes from job conflict and job burnout on employee loyalty and inadequate reward policy on employee performance.